Comparative analysis of CRP and PCT as biomarkers for early diagnosis of pediatric septic arthritis: superior performance of CRP - Xu, Wenchen; Yu, Piaoxue; Wang, Xiangxuan; Lin, Kainan; Chen, Hui (Frontiers in Pediatrics, 2025)
BackgroundSeptic arthritis is a severe pediatric infection that affects joint health and requires early diagnosis to prevent complications. Traditional methods have limitations, and although serum PCT shows promise as a diagnostic marker, its efficacy remains controversial, warranting further studies.ObjectiveTo investigate the value of C-reactive protein (CRP) and procalcitonin (PCT) in the early diagnosis of septic arthritis (SA) in pediatric patients and to compare their diagnostic efficiencies.MethodsThis investigation utilized a retrospective cohort methodology to ascertain and compare serum procalcitonin (PCT) and C-reactive protein (CRP) concentrations among a pediatric population comprising 29 individuals diagnosed with septic arthritis and 25 with non-septic arthritis (NSA), all of whom were admitted to our institutional facility over a three-year period from 2019 to 2021.ResultsCRP levels (>10 mg/L) were significantly higher in the septic arthritis group than in the non-septic group (26/29 vs. 3/25, P < 0.001), whereas PCT levels (>0.25 ng/ml) showed no significant difference (5/29 vs. 1/25, P = 0.385). ROC analysis revealed a high diagnostic performance for CRP (AUC 0.950, 95% CI 0.886–0.995, Youden index 88.6%) compared with PCT (AUC 0.574, 95% CI 0.417–0.731, Youden index 17.2%), indicating the superior sensitivity and specificity of CRP for early diagnosis of septic arthritis.ConclusionOur findings substantiate the substantial superiority of CRP for the early detection and preliminary alert of pediatric septic arthritis. However, due to the small sample size, its significant advantage over procalcitonin (PCT) requires confirmation in larger studies.